Refinement of the background ionospheric conditions and plausible explanation based on neutral dynamics for the occurrence/non-occurrence of L-band scintillation patches against forecast - Sridharan, R.; Jose, Lijo; Bagiya, Mala S.; Sunda, Surendra; Chaudhary, R. K. (My University, 2015)
The recently evolved L-band scintillation forecast mechanism based on the characteristic features of the daytime F-region electron density fluctuations and also on the basic ionospheric conditions had been successful to a reasonable extent in forecasting the spatio-temporal map of scintillation patches. There had been a few non-compliances in the expected pattern within/outside the forecast windows. The present paper attempts to address such non-compliances and offers a plausible explanation based on neutral dynamics, especially the local time variation of vertical winds over the magnetic equator, while at the same time refining the earlier stipulated background ionospheric conditions. With the above re- finements, it is anticipated that the forecast mechanism would become very robust. The present results highlight the importance of the neutral dynamical parameters and the urgent need to concentrate on the efforts to make systematic measurements of the same in order to characterize their variability.
Keywords: Ionosphere; L-band scintillation